Penerapan Sistem Informasi Pariwisata di Kabupaten Nias Selatan Menggunakan Metode User Centered Design (UCD) untuk Meningkatkan Aksesibilitas - Dessry Cantika Lase; Andi Marwan Elhanafi (Lembaga Pengembangan Kinerja Dosen, 2025)
The tourism sector has become a vital component of the economy, contributing significantly to the income of both regions and countries. In South Nias Regency, there are various unique tourism assets, such as the traditional Lompat Batu (Stone Jumping) ritual, distinctive traditional house architecture, colorful traditional costumes, and a series of breathtaking beaches that attract a large number of visitors. The region's strategic geographical location further enhances the potential for developing its tourism sector. However, despite the rich cultural and natural assets, the tourism sector in South Nias Regency faces challenges such as limited access to comprehensive and up-to-date information about tourist destinations. The need for an improved information system has become more urgent, as the current tourism data is fragmented, not fully integrated, and lacks interactive features. This makes it difficult for potential travelers to access accurate and reliable information regarding the region's attractions, accommodations, and travel tips. Therefore, this study proposes the development of a web-based Tourism Information System that utilizes a User-Centered Design (UCD) approach. The UCD methodology ensures that the system is developed with the end user in mind, focusing on user needs, ease of use, and efficient interaction at every phase of the design process. The proposed system aims to be responsive and user-friendly, providing travelers with a convenient platform to access accurate and geographically relevant tourism data. Through the system, users can easily explore various tourist spots, rate destinations, and read user reviews, which will improve their overall travel experience. The system also features an interactive map that allows visitors to visually locate attractions, accommodations, and other points of interest.